The effect of health claim information disclosure on the sensory characteristics of plant sterol-enriched turkey as assessed using the Check-All-That-Apply (CATA) methodology. (April 2017) - Grasso, S.; Monahan, F.J.; Hutchings, S.C.; Brunton, N.P.
Highlights: The effect of information disclosure on sensory evaluation of turkey was investigated. 80 untrained panellists evaluated processed turkey with & without added plant sterol. Plant sterol meat appearance acceptability increased after information disclosure. Information disclosure increased willingness to pay/to buy for plant sterol turkey. Differences in how CATA questions were used to describe the samples were identified. Abstract: CATA questions are becoming a popular, quick and easy tool to acquire consumer-based sensory product characterizations. This article combined CATA questions with health claim information disclosure to gather information on the acceptability, sensory characterisation by CATA, willingness to buy (WTB) and willingness to pay (WTP) of a novel carrier matrix-functional ingredient combination: deli-style turkey enriched with plant sterols. Control and plant sterol-enriched (SE) meat samples were evaluated by 80 untrained panellists in two scenarios: 1) blind (no information on the products), and 2) informed (information on plant sterols and associated European Food Safety Authority (EFSA) health claim). Acceptability of SE blind samples was significantly lower than control blind for appearance, texture and overall liking, but not for flavour. After information disclosure, there were no significant differences in the liking categories between control and SE samples, although information had more a negative effect on the liking of control samples than a positive effect on the liking of SE samples. Information disclosure had an effect on the panellists' choice of CATA terms: some terms discriminated control and SE samples in the blind condition, but did not discriminate the same samples after information disclosure ( uniform looking and unusual appearance, pale-whitish colour ); the opposite was true for other terms ( crumbly texture, strong and weak turkey flavour ). Penalty-lift analysis was affected by the health claim information disclosure. After information disclosure, panellists testified to a higher WTB and WTP for SE samples compared to control. Overall inclusion of EFSA plant sterol health claim information significantly increased appearance liking, WTB and WTP of SE samples while affecting the consumer sensory profiling by CATA before and after health claim information disclosure.